2021
DOI: 10.3390/ma14082053
|View full text |Cite
|
Sign up to set email alerts
|

High Electrochemical Performance Silicon Thin-Film Free-Standing Electrodes Based on Buckypaper for Flexible Lithium-Ion Batteries

Abstract: Recently, applications for lithium-ion batteries (LIBs) have expanded to include electric vehicles and electric energy storage systems, extending beyond power sources for portable electronic devices. The power sources of these flexible electronic devices require the creation of thin, light, and flexible power supply devices such as flexile electrolytes/insulators, electrode materials, current collectors, and batteries that play an important role in packaging. Demand will require the progress of modern electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The semicircle in the high frequency region represents the surface resistance of lithium ions passing through the interface, and the oblique line in the low frequency region represents the diffusion resistance of lithium ions. 29,30 It can be seen from the Figure 9 that as the carbonization temperature increased, the AC impedance of the flexible electrode decreased. When the carbonization temperature rised to 1000°C, the AC impedance of the flexible electrode reduced to 5 V. This is because with the increase of carbonization temperature, the better the carbonization effect of cotton fabric and the higher the conductivity.…”
Section: Resultsmentioning
confidence: 98%
“…The semicircle in the high frequency region represents the surface resistance of lithium ions passing through the interface, and the oblique line in the low frequency region represents the diffusion resistance of lithium ions. 29,30 It can be seen from the Figure 9 that as the carbonization temperature increased, the AC impedance of the flexible electrode decreased. When the carbonization temperature rised to 1000°C, the AC impedance of the flexible electrode reduced to 5 V. This is because with the increase of carbonization temperature, the better the carbonization effect of cotton fabric and the higher the conductivity.…”
Section: Resultsmentioning
confidence: 98%
“…For all three cathodes, the capacity decreases momentarily at high current densities with an increase in the proportion of the side reaction as a direct consequence of the Bulter-Volmer equation, resulting in a nonreversible reaction. 58,59 After the high rate (5C), the capacity recovery at the fundamental cycle rate of 0.2C indicates that the crystal structure is preserved. Further, the discharge capacities after 10 cycles at each C rate are 128, 119, 113, 105, 93, and 126 mA h g À1 for LMTO and 140, 138, 133, 125, 115, and 142 mA h g À1 for LMTOS, which are the highest.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Flexible batteries have received enormous attention recently, especially in healthcare and wearable electronics. 49 Our group previously reported 50 that due to the porous nature of buckypaper, Si nanoparticles adhere well to the buckypaper current collector upon coating.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, with buckypaper electrodes, flexible LIBs showed no signs of cracking, delamination, or structural changes typically observed in rigid LIBs. Flexible batteries have received enormous attention recently, especially in healthcare and wearable electronics . Our group previously reported that due to the porous nature of buckypaper, Si nanoparticles adhere well to the buckypaper current collector upon coating.…”
Section: Introductionmentioning
confidence: 99%